A Comparative Study of Cervical Cancer Early Detection by Using Visual Inspection with Acetic Acid (VIA) Method in Bandar Lampung in 2019 Concerning Breast Cancer and Cervical Cancer Mitigations - Febri Adriati; Aila Karyus; Achmad Djamil (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The visual inspection with acetic acid (VIA) test coverage in Bandar Lampung was 53.76% in 2019 and a pre-survey result showed that VIA implementation in Bandar Lampung was not yet optimal. The problem in this research was to do a comparative study on the cervical cancer earlier detection by using VIA method in Bandar Lampung according to the Regulation of Ministry of Health No. 29 in 2017 concerning breast cancer and cervical cancer mitigations. This was a comparative study by using r-test (Pearson Product Moment). The result showed a weak correlation between VIA equipment amounts to VIA test coverage in Bandar Lampung, a strong correlation between trained human resource amount to VIA test coverage in Bandar Lampung, a moderate correlation between numbers of examination and VIA coverage in Bandar Lampung, and moderate correlation between numbers of information technique activities and VIA coverage in Bandar Lampung. The most dominant factor was trained human resources.